Identification of a domain within the phosphoprotein of vesicular stomatitis virus that is essential for transcription in vitro. - Gill, D S (1986)
A full-length cDNA copy of the phosphoprotein (NS) mRNA of vesicular stomatitis virus (New Jersey serotype) was inserted into pGEM4 vector downstream of the promoter for bacteriophage SP6 RNA polymerase. Transcription of the cDNA in vitro resulted in the synthesis of NS mRNA, which was subsequently translated into NS protein in a cell-free rabbit reticulocyte system. The biological activity of the expressed NS protein was demonstrated by in vitro synthesis of mRNA by transcription-reconstitution with purified viral L protein and N-RNA template. Deletion mapping of the NS gene defined a specific domain between amino acid residues 213 and 247, which was essential for in vitro transcription. Removal of the COOH-terminal 21 amino acids, on the other hand, did not have a significant effect on transcription. This domain appears to be involved in efficient binding of NS protein to the N protein-RNA template.